2019
DOI: 10.1248/yakushi.19-00084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rheological Properties of Cohesive Ophthalmic Viscosurgical Devices Composed of Sodium Hyaluronate with High Molecular Weight—2019

Abstract: Ophthalmic viscosurgical devices (OVDs), mainly containing sodium hyaluronate (HA), are used in cataract surgeries to protect the cornea endothelium. In this study, the rheological properties of 9 launched products (containing 1% HA) were evaluated. The molecular weights (MWs) of HA estimated based on intrinsic viscosity varied widely, between 1100 2500 kDa, and showed a particular value for each product. Of the 9 products, 6 are classiˆed as cohesive OVDs and their product speciˆcations show the same value f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…We previously reported that the OVDs tested in this study had specific rheological properties even when they were of the same composition or classification type [14,15]. Here, we clarified the advantages and disadvantages of each OVD for the wet shell technique on the basis of their properties.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We previously reported that the OVDs tested in this study had specific rheological properties even when they were of the same composition or classification type [14,15]. Here, we clarified the advantages and disadvantages of each OVD for the wet shell technique on the basis of their properties.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, Opelead, Viscoat, and Shellgan were classified into such a category ( Table 2). We previously evaluated the physical properties of these OVD products and demonstrated that their basic properties were different even though they belonged to the same category [14,15]. We have speculated that the molecular weight (Mw) and concentration of HA, which is the main component of OVDs, have a great influence on rheological properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is measured in the ease of injection of the material and is crucial for the mobilizing effects of OVDs during surgery. It is important to note that the viscosity of an OVD is higher when the molecular weight at low shear rate increases [ 17 ]. Viscoelasticity: it describes the elastic component of the OVD.…”
Section: Types Of Ovdmentioning
confidence: 99%
“…[8][9][10] Ophthalmic researchers have concluded that retention durability is one of the important properties of OVDs during ocular surgery not only in the intraocular space but also on the ocular surface. [9][10][11][12][13] Previously, we have demonstrated that OVD products have their own rheological properties, even if their product specifications are the same value. 14,15) We have considered that rheological properties, which are not estimated so far, might also influence the retention durability of OVDs not only on the corneal surface but also in the eye.…”
Section: Introductionmentioning
confidence: 99%